Palladium-Catalyzed Hydroalkylation of Alkoxyallenes Using Monofluorinated Nucleophiles - Liao, Ling; Zhao, Zhi-Peng; Gu, Bo-Ning; Yu, Jin-Sheng; Zhou, Jian (Synthesis, 2023)
A branch-selective hydroalkylation of alkoxyallenes with monofluorinated nucleophiles was developed using palladium catalysis, allowing construction of valuable α-monofluoroalkylated allylic ethers. Notably, this represents the first catalytic hydrofluoroalkylation of alkoxyallenes. The practicability of this method is highlighted by its broad substrate scope and diversified product elaborations. Initial investigation of the asymmetric variant could afford chiral fluorine-containing allylic ethers with up to 68% ee.
Keywords: palladium catalysis; alkoxyallenes; hydrofluoroalkylation; branch-selectivity; fluorine